2022
DOI: 10.3390/jcm11030473
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Signaling Secretome of Platelet-Rich Plasma: Towards a Better Understanding of Its Therapeutic Potential in Knee Osteoarthritis

Abstract: Platelets and their secretory products play an important role in determining the balance between tissue repair and tissue damage. To obtain novel insights into the molecular composition of platelet-rich plasma (PRP) and contextualize them in knee osteoarthritis (OA), two different plasma formulations, namely PRP and platelet-poor plasma (PPP), were prepared from six healthy donors following a biobank-automated protocol. Inter-donor differences were analyzed, and pools were created before performing multiplexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…PRP is an autologous biological product containing numerous bioactive proteins such as growth factors (IGF, TGF, VEGF, PDGF, etc. ), cytokines, and chemokines, which have the potential to play therapeutic roles in a variety of treatments, including musculoskeletal conditions, gynecology, urology, plastic surgery, ophthalmology, and dermatology, while its production remains easy, fast, and quite cheap to set up [ 9 , 10 , 11 ]. Indeed, PRP is simply obtained by the centrifugation of anticoagulated whole blood, allowing separation of plasma and platelets and having the lowest densities compared to red blood cells (RBCs) and leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…PRP is an autologous biological product containing numerous bioactive proteins such as growth factors (IGF, TGF, VEGF, PDGF, etc. ), cytokines, and chemokines, which have the potential to play therapeutic roles in a variety of treatments, including musculoskeletal conditions, gynecology, urology, plastic surgery, ophthalmology, and dermatology, while its production remains easy, fast, and quite cheap to set up [ 9 , 10 , 11 ]. Indeed, PRP is simply obtained by the centrifugation of anticoagulated whole blood, allowing separation of plasma and platelets and having the lowest densities compared to red blood cells (RBCs) and leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study [ 53 ], we showed that the molecular intricacy of PRP by far exceeds that of PPP. In fact, platelet secretome contains a pool of chemokines, growth factors and interleukins, which are synthesized in the bone marrow by their parent cell, the megakaryocyte.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Protein arrays followed by bioinformatic analyses have revealed an association between platelet secretome and osteoarthritis canonical pathway. 65 These analyses also predicted the participation of platelet secretome in specific inflammatory pathways, including neuroinflammation, IL-17, IL-6, IL-8, and high-mobility group box 1 signaling. 65 The molecular intricacies of PRP in immune cell modulation are depicted in Figure 1.…”
Section: Inflammation and Pain As Potential Targets For Prpsmentioning
confidence: 96%
“…65 These analyses also predicted the participation of platelet secretome in specific inflammatory pathways, including neuroinflammation, IL-17, IL-6, IL-8, and high-mobility group box 1 signaling. 65 The molecular intricacies of PRP in immune cell modulation are depicted in Figure 1.…”
Section: Inflammation and Pain As Potential Targets For Prpsmentioning
confidence: 96%